Nonaqueous Microemulsion in the Bmim Tf2N/Brij 30/ n-Nonane System Structural Investigation and Application as Gold Nanoparticle Microreactor - Mamusa, Marianna (Langmuir : the ACS journal of surfaces and colloids, 2018)
Microemulsions based on ionic liquids (ILs) are being increasingly studied in many different areas of physical chemistry because of the attractive properties of ILs. In particular, waterless microemulsions where the IL represents the polar phase can be of interest for those applications that demand the nanosegregation of polar substances, but in which the absence of water is a strict requirement. In this work, we prepared a reverse, nonaqueous microemulsion based on the low-viscosity room-temperature IL, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide , the surfactant Brij 30, and n-nonane. The systems were characterized by dynamic light scattering and small-angle X-ray scattering; the IL/oil microemulsion was further employed as a templating system for the synthesis of gold nanoparticles from hydrogen tetrachloroaurate(III), HAuCl4, by UV-photoreduction technique